The Halloween tree - Bradbury, Ray, 1920-; Mugnaini, Joseph A. (New York, Yearling Books, 1972)
A group of children and a "spirit" go back through time to discover the beginnings of Halloween.
Accelerated Reader AR
Keywords: Time travel -- Fiction; Halloween -- Fiction